2014
DOI: 10.1103/physrevlett.113.076408
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Density-Matrix Topological Fermionic Phases: Topological Uhlmann Numbers

Abstract: We construct a topological invariant that classifies density matrices of symmetry-protected topological orders in two-dimensional fermionic systems. As it is constructed out of the previously introduced Uhlmann phase, we refer to it as the topological Uhlmann number nU. With it, we study thermal topological phases in several two-dimensional models of topological insulators and superconductors, computing phase diagrams where the temperature T is on an equal footing with the coupling constants in the Hamiltonian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 52 publications
3
131
1
Order By: Relevance
“…In Section III, topological invariants for density matrices with various spectral assumptions are defined. We compare the present approach to the construction of Uhlmann phase winding numbers that have recently been proposed [24,25] to classify thermal Chern insulators in Section IV. Concluding remarks are presented in Section V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Section III, topological invariants for density matrices with various spectral assumptions are defined. We compare the present approach to the construction of Uhlmann phase winding numbers that have recently been proposed [24,25] to classify thermal Chern insulators in Section IV. Concluding remarks are presented in Section V.…”
Section: Introductionmentioning
confidence: 99%
“…As both k x in the BZ and the phase φ kx U are defined on a circle, the mapping k x → φ kx U is characterized by an integer quantized winding number which is exactly measured by Eq. (25).…”
mentioning
confidence: 99%
“…Recently, there have been some advances in this direction. [243][244][245][246][247][248][249][250][251][252][253] The effects of superconducting fluctuations on Majorana fermion states have also been studied recently. [254][255][256][257] It was revealed that the topological degeneracy associated with Majorana fermions is maintained even for the case of quasi-long-range order with power-law decay of the superconducting correlation, for which the total electron charge is conserved, and the phase of the superconducting gap fluctuates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical work also shows that there is a precise sense in which finite temperature topological phases retain a quantized invariant. 64,65 With the caveats mentioned earlier regarding the magnetic order in the strong coupling regime, one may discuss a finite temperature phase diagram for our model that includes both topological phases and magnetic phases.…”
Section: A Hopping Parameter-driven Topological Phase Transitionmentioning
confidence: 99%
“…Thus, it is highly desirable to investigate the effect of interactions on topological systems, particularly at finite temperature, which is important and relevant to real materials. Recent work has shown that a finite-temperature topological invariant can be defined 64,65 , which effectively extends the notation of topological phases to finite temperatures.…”
Section: Introductionmentioning
confidence: 98%